In vitro gastrointestinal digestion of pomegranate peel (Punica granatum) flour obtained from co-products: Changes in the antioxidant potential and bioactive compounds stability - Gullon, Beatriz; Pintado, Manuela E.; Fernández-López, Juana; Pérez-Álvarez, José A.; Viuda-Martos, Manuel (Journal of functional foods, 2015)
•In vitro gastrointestinal digestion (GID) of pomegranate peel flour (PPF) was analysed.•Polyphenolic compounds were sustained and released from PPF.•Flavonoids bioaccessibility was higher than phenolic compounds.•PPF showed antioxidant activity in each step of GID.•The antioxidant activity could be attributed to the high content of polyphenolic compounds. The effect of in vitro gastrointestinal digestion (GID) on the recovery, bioaccessibility and stability of polyphenolic compounds, the changes in antioxidant activity and the short chain fatty acids (SCFAs) production of pomegranate peel flour (PPF) were evaluated. The extracts obtained in each step of GID were used to determine the stability of polyphenolic profile using HPLC whilst the antioxidant properties were determined using five methodologies. The SCFAs production from PPF fermentation was also determined. At the end of GID process, the bioaccessibility of phenolic and flavonoid compounds was 35.90 and 64.02%, respectively. The polyphenolic compounds decreased after GID except that for ellagic acid which increased. GID increased the chelating activity and reducing power. However, the scavenging properties were reduced. Fermentation of PPF by colonic bacteria generated acetic, propionic and butyric acids. PPF could be used in the food industry as a potential ingredient to develop functional foods that promote health benefits.